Evaluation of the CIPP Model for Education and Training Program at the National Archives Indonesia (ANRI) - Setyo Edy Susanto; Soewarto Hardhienata; Widodo Sunaryo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Lack of training and implementation effectiveness require proper evaluation and monitoring. This study aims to evaluate education and training programs at the National Archives of the Republic of Indonesia (ANRI). The type of evaluation used is the CIPP method. The results of the evaluation research stated that education and training at the National Archives Institute had good results. The evaluation of the context, inputs, programs, and products in the implementation of training at the ANRI institution had good results. All evaluation bases require continuous attention so that the evaluation results for the next program will still produce a good category.